2017
DOI: 10.2340/16501977-2270
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of venous thromboembolism events during acute inpatient rehabilitation in a comprehensive cancer centre

Abstract: Cancer patients with low FIM transfer scores and lower extremity oedema are at higher risk of venous thromboembolism. Patients with these clinical findings at admission may require measures for more aggressive surveillance for the presence of venous thromboembolism. Patients with venous thromboembolism had an increased length of stay in rehabilitation, but ultimately did not have significant differences in FIM score changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In this study, 22 out of 374 total patients (5.9%) had deep vein thrombosis; 10 were found to have deep vein thrombosis while in rehabilitation and 12 patients had deep vein thrombosis during the acute phase of the hospitalisation, similar to earlier findings (Ng et al, 2017). These results are similar to earlier findings where 5% of cancer patients undergoing rehabilitation were found to have acute venous thrombosis (Ng et al, 2017). Patients included those who are at high risk for deep vein thrombosis because of cancer, high immobility, recent surgical procedures and chemotherapy treatment.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, 22 out of 374 total patients (5.9%) had deep vein thrombosis; 10 were found to have deep vein thrombosis while in rehabilitation and 12 patients had deep vein thrombosis during the acute phase of the hospitalisation, similar to earlier findings (Ng et al, 2017). These results are similar to earlier findings where 5% of cancer patients undergoing rehabilitation were found to have acute venous thrombosis (Ng et al, 2017). Patients included those who are at high risk for deep vein thrombosis because of cancer, high immobility, recent surgical procedures and chemotherapy treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study by Ng et al (2017), it was reported that 5.2% of cancer patients were affected with venous thromboembolism during the course of rehabilitation. Patients who were found to have lower extremity oedema at admission (P=0.02) had Calf measurements screening for deep vein thrombosis in acute inpatient cancer rehabilitation…”
mentioning
confidence: 96%
See 3 more Smart Citations